Smokin' : recipes for smoking ribs, salmon, chicken, mozzarella, and more, with your stovetop smoker /: recipes for smoking ribs, salmon, chicken, mozzarella, and more, with your stovetop smoker. ([2004]) - Unknown
No abstract available